2017
DOI: 10.1590/0074-02760160394
|View full text |Cite
|
Sign up to set email alerts
|

Poor sensitivity of rapid tests for the detection of antibodies to the hepatitis B virus: implications for field studies

Abstract: Rapid tests (RTs) can be used as an alternative method for the conventional diagnosis of hepatitis B virus (HBV). This study aims to evaluate antibodies to HBsAg (anti-HBs) and antibodies to HBeAg (anti-HBe) RTs under different Brazilian settings. The following three groups were included: GI: viral hepatitis outpatient services; GII: low resource areas; and GIII: crack users and beauticians. Imuno-rápido anti-HBsAg™ and Imuno-rápido anti-HBeAg™ RTs were evaluated and showed specificities greater than 95% in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…The prevalence in this finding is higher when compared to the previous studies in different region of Ethiopia, like, 3.5% in Dawuro zone [12], 4.3% in Arbaminch Hospital [5], Dessie Referral Hospital, 4.9% [1], Adjibar Rural Health Center, Northeast Ethiopia 3.8% [15]. This might different sampling technique, sample processing techmique and existence of harmful traditional practice before years.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence in this finding is higher when compared to the previous studies in different region of Ethiopia, like, 3.5% in Dawuro zone [12], 4.3% in Arbaminch Hospital [5], Dessie Referral Hospital, 4.9% [1], Adjibar Rural Health Center, Northeast Ethiopia 3.8% [15]. This might different sampling technique, sample processing techmique and existence of harmful traditional practice before years.…”
Section: Discussionmentioning
confidence: 57%
“…Hepatitis B surface antibody (anti-HBs) is the key marker to determine an individual’s immunity status to hepatitis B virus and triage the need for vaccination. A few anti-HBs POCs are commercially available, but most have poor reported sensitivity ranging from 20% to 70% [ 33 , 80 , 81 , 82 ]. One study reported a sensitivity of 91.8% using an anti-HBs rapid test card among 1272 samples [ 70 ]; however, these findings require further validation.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…Several HBeAg POCs are commercially available; however, published data show the accuracy of HBeAg POCs has a wide range, with sensitivity of 30–82% and specificity of 67–100% [ 33 , 80 , 88 ]. Similarly, Anti-HBe POCs are reported to have poor sensitivity but excellent specificity in studies [ 33 , 81 ]. Given the high costs and challenges in accessing HBV DNA testing in low-resource settings, the WHO recommends HBeAg to triage treatment [ 83 , 89 , 90 ]; therefore, the low testing accuracy of HBeAg POCs is an urgent issue to be addressed.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…The laboratory method used in this study was the immunochromatographic technology-based rapid assay due to its suitability for the investigation and screening at the population level, in endemic areas or in vulnerable groups. This method's advantages are the low cost, high specificity, rapid test processing, easy technical features, diagnosis efficiency, high patient's acceptance, and no need for a laboratory infrastructure [38][39][40] . Further, we chose this technology based on the WHO's guidelines to track the HBV antigen and antibody levels and to eliminate hepatitis B as one of the main threats to public health 3 .…”
Section: Discussionmentioning
confidence: 99%